Mixed-meal challenge differentially modulates metabolic pathways in adipose tissue in healthy abdominally obese subjects with high versus low liver fat: a secondary analysis of a randomized clinical trial. - Fang, Yan; Hooiveld, Guido J. E. J.; Afman, Lydia A. (Nutrition & Metabolism, 2025)
Background: Increased liver fat increases the risk of chronic metabolic diseases. This study is an exploratory secondary analysis aimed at (1) investigating whether transcriptomic responses of abdominal subcutaneous adipose tissue (SAT) to a high-fat-high-glucose meal challenge differ according to varying levels of liver fat accumulation and (2) identifying pathways in abdominal SAT metabolism that may be related to liver fat accumulation. We examined differences in abdominal SAT gene expression and pathway activity both at fasting and in response to a mixed-meal challenge, comparing individuals with varying levels of liver fat. Method: From the subset of 66 of 110 middle-aged participants of a previous intervention study, we grouped participants by tertiles of intrahepatic lipids (IHL) into high liver fat group (n = 22, IHL: 8.0%-32.6%), middle liver fat group (n = 22, IHL: 2.5%-8.0%) and low liver fat group (n = 22, IHL: 0.1%-2.5%). Participants received a high-fat-high-glucose mixed-meal challenge (3833 kJ). Abdominal SAT samples were collected before and 4 h after the challenge for microarray gene expression analysis. Results: At fasting, 87 gene sets were differently expressed (FDR < 0.25) between the high and the low liver fat group, and 66 gene sets were differently expressed between the high and middle liver fat group, pathways related to energy metabolism were lower expressed in the high compared to the low liver fat group. Postprandially, 17 gene sets responded differently to the mixed meal challenge, of which 7 changed within the high liver fat group, 2 changed within the middle liver fat group and 4 within the low liver fat group. The challenge increased the expression of genes involved in oxidative phosphorylation more in the high compared to the low liver fat group. Conclusions: Compared to individuals with low liver fat, individuals with high liver fat have lower gene expression but a higher response of energy-related pathways in abdominal SAT at fasting and after a high-fat-high-glucose challenge. Whether this is the cause or consequence of increased liver fat storage or an early stage of insulin resistance needs to be investigated. Trial registration: This trial was registered at clinicaltrials.gov as NCT02194504.